Influence of Diet on the Effect of the Probiotic Lactobacillus paracasei in Rats Suffering From Allergic Asthma - Xie, Ao; Song, Jiaping; Lu, Shan; Liu, Yinhui; Tang, Li; Wen, Shu (Frontiers in Microbiology, 2021)
Mounting evidence suggests that probiotics can be used to treat allergic asthma by modulating the gut microbiota, and that the effects of probiotics may be influenced by environmental factors such as diet. We conducted a rat model with allergic asthma (AA) modulated by Lactobacillus paracasei, feeding up with high-fat or high-fiber diets based on collecting data from 85 questionnaires. The systemic proinflammatory cytokines were detected by ELISA and the overall structure of fecal microbiota was analyzed via 16S rRNA gene sequencing. The results showed consumption of a high-fiber diet alleviated the allergic symptoms and airway inflammation, and led to improving the imbalance of T-helper type 1 (Th1)/Th2 cells with increased expression of interferon-γ and decreased expression of interleukin-4. Whereas, the high-fat diet had deteriorating implications and skewed the inflammatory perturbation. Furthermore, abundances of phylum Bacteroidetes, families Muribaculaceae, Tannerellaceae, Prevotellaceae, Enterococcaceae, genera Allobaculum, Parabacteroides, and Enterococcus were enriched in L. paracasei-modulating rats fed with high-fiber diet. Firmicutes and Proteobacteria, families Lachnospiraceae, Ruminococcaceae and Desulfovibrionaceae, genera Blautia, unidentified_Ruminococcaceae, unidentified_Clostridiales and Oscillibacter were in relatively high abundance in the rats administered high-fat diet. Association between changed microbiota and inflammatory cytokines was also conferred. These data indicated that the efficacy of L. paracasei in allergic asthma was influenced by different dietary patterns. Hence, diet is important for probiotic therapy when managing allergic asthma.